2020
DOI: 10.1108/srj-12-2016-0224
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate social performance disclosure: a literature review

Abstract: Purpose This review aims to identify the determinants of voluntary disclosure of corporate social performance (CSP) and to analyze and consolidate previous quantitative studies to identify the theoretical perspectives and the variables used in measuring the determinants of CSP disclosure (CSP-D). Design/methodology/approach A literature review of articles published from 1987 to 2015 was conducted using the three databases, Ebsco, ISI and Jstor, with CSP-D as the dependent variable. The goal was to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 107 publications
0
33
0
7
Order By: Relevance
“…Over the last two decades, several studies on CSR disclosure have contributed to further theoretical development and their practical application in the business world. This research is based on two theories: legitimacy and agency theories (Garcia et al, 2020). From the legitimacy perspective, companies' CSR disclosure practices constitute a tool for establishing and maintaining their legitimacy because CSR affects several important stakeholders (Tilt & Symes, 1999).…”
Section: Csr Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last two decades, several studies on CSR disclosure have contributed to further theoretical development and their practical application in the business world. This research is based on two theories: legitimacy and agency theories (Garcia et al, 2020). From the legitimacy perspective, companies' CSR disclosure practices constitute a tool for establishing and maintaining their legitimacy because CSR affects several important stakeholders (Tilt & Symes, 1999).…”
Section: Csr Theoretical Backgroundmentioning
confidence: 99%
“…Recently, many studies have indicated growing interest in CSR disclosure (e.g. Alazzani et al, 2019;Garcia et al, 2020). Researchers argue that it performs a vital function in enhancing the quality of communication among stakeholders (De Klerk et al, 2015).…”
Section: Csr Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous literature related to the role of government in promoting CSR activities (Campbell, 2007;Aguilera et al, 2007;Steurer, 2010;Škare and Golja, 2014) and Milne, 1996;Bansal and Roth, 2000;Brønn and Vidaver-Cohen, 2009;MnifSellami et al, 2019;Garcia et al, 2020). These studies have been conducted mainly in developed countries and they have been quite varied.…”
Section: Case Of Tunisian Companiesmentioning
confidence: 99%
“…The "Results and Discussion" section contains the results and discussion, while the article is concluded in the "Conclusion" section. Garcia et al (2020) investigated and analyzed the determinants of voluntary disclosure of corporate social performance (CSP) through a literature review of articles in EBSCO, ISI, and JSTOR databases published from 1987 to 2015, to discover the theoretical perspectives and the variables used in measuring the determinants of CSP disclosure (the independent variables). They confirmed that there was no single explanation for what determined CSP disclosure, and the theories that support a relationship between CSP disclosure and its determinants are legitimacy, institutional, stakeholder, agency, and voluntary disclosure.…”
Section: Introductionmentioning
confidence: 99%